2014
DOI: 10.1590/0074-0276140279
|View full text |Cite
|
Sign up to set email alerts
|

CagA phosphorylation EPIYA-C motifs and the vacA i genotype in Helicobacter pylori strains of asymptomatic children from a high-risk gastric cancer area in northeastern Brazil

Abstract: Helicobacter pylori infection is one of the most common infections worldwide and is associated with gastric diseases. Virulence factors such as VacA and CagA have been shown to increase the risk of these diseases. Studies have suggested a causal role of CagA EPIYA-C in gastric carcinogenesis and this factor has been shown to be geographically diverse. We investigated the number of CagA EPIYA motifs and the vacA i genotypes in H. pylori strains from asymptomatic children. We included samples from 40 infected ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…We did not observe any clinical association between the motifs and gastritis and peptic ulcer which is consistent with some studies [ 26 , 32 ] conducted in Iran but in disagreement with a study in Iran [ 1 ]and two studies in Mexico [ 14 ]and Brazil [ 36 ]. Our study showed that increased C fragments cannot increase pathogenicity; however, the number of motifs with two and more C fragments was very low and the prevalence rates and distributions of gastritis and peptic ulcer very high in our study, which is consistent with Ogordnik and Hossein & and Shekarzadeh [ 35 ] studies, but Vianna [ 36 ], Salih [ 34 ], Gonzalo [ 43 ], Basso [ 42 ] and Kalaf [ 44 ] have reported that increased C fragment was associated with clinical symptoms.…”
Section: Resultssupporting
confidence: 90%
“…We did not observe any clinical association between the motifs and gastritis and peptic ulcer which is consistent with some studies [ 26 , 32 ] conducted in Iran but in disagreement with a study in Iran [ 1 ]and two studies in Mexico [ 14 ]and Brazil [ 36 ]. Our study showed that increased C fragments cannot increase pathogenicity; however, the number of motifs with two and more C fragments was very low and the prevalence rates and distributions of gastritis and peptic ulcer very high in our study, which is consistent with Ogordnik and Hossein & and Shekarzadeh [ 35 ] studies, but Vianna [ 36 ], Salih [ 34 ], Gonzalo [ 43 ], Basso [ 42 ] and Kalaf [ 44 ] have reported that increased C fragment was associated with clinical symptoms.…”
Section: Resultssupporting
confidence: 90%
“…Children: In children, the frequency of the oipA “on” status tends to be somewhat lower than in adults (49.6%, 67.6% and 68.8% in children from Portugal, United States and Brazil, respectively)[22,30,41], with higher frequencies among pediatric strains from high risk populations in which the incidence of H. pylori infection and related disease is significant. Moreover, the OR for PUD risk was shown to be higher in children (OR= 7.03, 95%CI: 3.71-13.34) compared to that in adults, suggesting increased risk for PUD in children with oipA “on” status[40,42].…”
Section: Genes Encoding Outer Membrane Proteinsmentioning
confidence: 99%
“…Brazil has a population of over 200 million individuals with varying ethnic and geographic backgrounds. The country is heterogeneous with respect to sanitary coverage, and a large proportion of its population still do not have access to highquality water 9,10 . Access to high-quality water is not evenly distributed across Brazil and is highly dependent on sanitary facilities and infrastructure.…”
Section: Introductionmentioning
confidence: 99%